Heidegger's confessions: The Remains of Saint Augustine in Being and Time & Beyond - Coyne, Ryan (Religion and postmodernism, 2015)
Heidegger's Paul -- The cogito out-of-reach -- The remains of Christian theology -- Testimony and the irretrievable in being and time -- Temporality and transformation, or Augustine through the turn -- On retraction -- Conclusion : difference and de-theologization